2019
DOI: 10.3389/fneur.2019.01032
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Baseline Neutrophil-to-Lymphocyte Ratio in Patients With Ischemic Stroke or Hemorrhagic Stroke: An Updated Meta-Analysis

Abstract: Background and purpose: Stroke is a leading cause of death and acquired disability in adults today. Inflammation plays an important role in the pathophysiology of stroke. The peripheral neutrophil-to-lymphocyte ratio (NLR) is an important global inflammatory indicator becoming more mainstream in stroke care. This meta-analysis aims to evaluate the relationship between the baseline NLR and acute ischemic and hemorrhagic stroke, as well as define the clinical significance of NLR in subtypes of ischemic stroke.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
98
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(116 citation statements)
references
References 78 publications
(67 reference statements)
9
98
1
2
Order By: Relevance
“…As previously discussed, the changes in peripheral leukocyte counts may be epiphenomenal to brain damage. However, previous studies have revealed that higher leukocyte counts in healthy patients are also associated with the increased risk of ischemic stroke events [2,32]. Further investigation may clarify how peripheral leukocyte counts are related to the risk of suffering an LVO is AIS, or how it may affect the composition of the thrombi.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…As previously discussed, the changes in peripheral leukocyte counts may be epiphenomenal to brain damage. However, previous studies have revealed that higher leukocyte counts in healthy patients are also associated with the increased risk of ischemic stroke events [2,32]. Further investigation may clarify how peripheral leukocyte counts are related to the risk of suffering an LVO is AIS, or how it may affect the composition of the thrombi.…”
Section: Discussionmentioning
confidence: 92%
“…Ischemic brain damage elicits systematic inflammatory response and cause a time-dependent activation of peripheral immune cells [1]. Leukocyte counts and ratios (such as neutrophilto-lymphocyte ratio) in peripheral blood proved to have good prognostic value to predict outcomes and post-stroke complications [2,3]. Higher leukocyte counts, especially neutrophil elevation is also associated with increasing severity and larger infarct volumes in AIS [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…As previously discussed, the changes in peripheral leukocyte counts may be epiphenomenal to brain damage. However, previous studies have revealed that higher leukocyte counts in healthy patients are also associated with the increased risk of ischemic stroke events [2,26]. Further investigation may clarify how peripheral leukocyte counts are related to the risk of suffering an LVO is AIS, or how it may affect the composition of the thrombi.…”
Section: Discussionmentioning
confidence: 92%
“…Ischemic brain damage elicits systematic in ammatory response and cause a time-dependent activation of peripheral immune cells [1]. Leukocyte counts and ratios (such as neutrophil-to-lymphocyte ratio) in peripheral blood proved to have good prognostic value to predict outcomes and post-stroke complications [2,3]. Higher leukocyte counts, especially neutrophil elevation is also associated with increasing severity and larger infarct volumes in AIS [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The neutrophil to lymphocyte ratio (NLR), as a simple parameter of innate (neutrophil), and adaptive (lymphocyte) immune response, is easy to obtain from peripheral blood (12). Recent studies show NLR can predict the prognosis and mortality of patients with aortic dissection or cerebral infarction (5, 13,14).…”
Section: Introductionmentioning
confidence: 99%